Bush Garden - Gignac, Danielle (University of Waterloo, 2014)
To garden is to draw with the land. This tending is the primary act of culture: to perpetuate a people by negotiating with a place. Gardening impresses hope upon the land, measuring the bounds of sustenance. A boundary is a necessary condition for a garden. I argue in this thesis that the boundaries of the garden are not always tangible. Indeed, in the case of the James Bay Cree, physical enclosures traditionally held little purpose in their way of life. Through gardening in numerous contexts, I have experienced land not as a commodity, but as a place to cultivate complex relationships. From this understanding, supported by literature and time spent with a First Nations community, I have come to approach “the bush” of the Cree as a garden in the fullest sense. In this thesis, I first describe a number of externally imposed boundaries that have contributed to the present conditions in remote northern communities. I then position the landscape of the Omushkego Cree of the James Bay Lowlands within negotiable moral boundaries, founded upon reciprocal relationships between a people and a land. These relationships are manifest in the words and markings that trace indigenous movement over the land, which centre around the harvest of food. Through narrative, this text unfolds the map of tradition in which food is a gift from the land, from mythical beginnings to current concerns, taking the practice of gardening as a measure of the Omushkego Cree's relationship to their land.